EFEITO DO RANELATO DE ESTRÔNCIO NA PROGRESSÃO DA PERDA ÓSSEA ALVEOLAR E PARÂMETROS CARDIOVASCULARES. EFEITO DO RANELATO DE ESTRÔNCIO NA PROGRESSÃO DA PERDA ÓSSEA ALVEOLAR E PARÂMETROS CARDIOVASCULARES. ESTUDO IN VIVO - Vilela, Ana Paula (2017)
Periodontal disease (PD) can be characterized as a chronic inflammatory disease in which there is destruction of the supporting tissues of the tooth. In its pathogenesis, the presence of a biofilm triggers a local immune-inflammatory response, with the production of pro-inflammatory mediators and cellular activation; consequently bone reabsorption and collagen degradation. Regarding the therapy of PD constant academic studies have been conducted in the search for alternative treatment. In this context, strontium ranelate (SR), drug currently used in the treatment of osteoporosis, represents a study target since it has biological properties on the bone tissue, such as effective reduction of reabsorption and increase of bone neoformation. Thus, the objective of this study was to evaluate the effect of SR on alveolar bone loss induced by the ligation method in rats. In addition, the cardiovascular safety profile of SE was ensured by the evaluation of blood pressure, heart rate and vascular reactivity. For these purposes, 30 rats (Wistar / 200-300g) were divided into three groups (n = 10 animals / group): G1) Control Group - No ligature / No treatment (placebo, 0.9% NaCl, via gavage); G2) Ligature group - With ligature / No treatment (placebo, 0.9% NaCl, via gavage); G3) Group Ligature + Strontium Ranelate - With ligation / With treatment (RE, 625mg / kg / day, via gavage). Alveolar bone loss was induced by the ligature method and the experimental time was 15 days. After this period, the animals were submitted to: (1) Morphometric quantification of alveolar bone loss; (2) Histological measurement (picrosirius) of tissue collagen; (3) Total alkaline phosphatase serum dosage and (4) Evaluation of cardiovascular parameters (blood pressure, heart rate and vascular reactivity). Comparing the means between groups using the parametric ANOVA test, followed by Tukey post hoc, performed statistical analysis. The level of significance was 5%. In the group in which the animals received SE treatment (G3) there was a significant decrease in alveolar bone loss, accompanied by a preservation of the periodontal collagen fibers. In addition, the alkaline phosphatase total levels were elevated in the G3 group. No changes were observed in the cardiovascular parameters evaluated.Although, additional studies are required, the results demonstrate that strontium ranelate represents an effective and therefore promising drug in PD therapy, reducing alveolar bone loss and tissue collagen degradation.